Fluoride Pharmacokinetics in Urine and Plasma Following Multiple Doses of MK‐8507, an Investigational, Oral, Once‐Weekly Nonnucleoside Reverse Transcriptase Inhibitor. (12th November 2021) - Gillespie, Gillian; Jackson Rudd, Deanne; Zhang, Saijuan; Schaeffer, Andrea; Tomek, Charles; Larson, Patrick; Stoch, S. Aubrey; Iwamoto, Marian
Abstract: MK‐8507 is an investigational HIV‐1 nonnucleoside reverse transcriptase inhibitor being developed for the treatment of HIV‐1 infection. MK‐8507 contains 2 trifluoromethyl groups that may result in fluoride release through metabolism, but the extent of MK‐8507–related fluoride release in humans has yet to be determined. This double‐blind, placebo‐controlled, 2‐period, parallel‐group, multiple‐dose trial in healthy participants without HIV‐1 who were administered a fluoride‐restricted diet and once‐weekly doses of MK‐8507 aimed to estimate the relationship between MK‐8507 dose and fluoride exposure. A total of 15 adult male and 3 adult female (of non‐childbearing potential) participants were randomized to receive MK‐8507 200 mg (n = 6), MK‐8507 800 mg (n = 6), or placebo (n = 6). Change from baseline in mean daily fluoride excretion averaged over 7 days following the administration of MK‐8507 200 mg resulted in a net mean increase of 19.8 μmol (90% confidence interval, 12.2‐27.4) relative to placebo and did not exceed 57 μmol, a threshold related to the mean difference between the daily reference dose set by the US Environmental Protection Agency and the average dietary fluoride intake in the United States. However, daily urinary fluoride excretion exceeded the threshold following administration of 800 mg MK‐8507 (75.1 μmol [90% confidence interval, 67.5‐82.7]). Assuming a linear relationship between MK‐8507 dose and estimated mean daily fluoride released at steady‐state, data interpolation suggests that the US Environmental Protection Agency reference dose for fluoride would not be exceeded in most patients when administering MK‐8507 at doses currently under clinical investigation (≤400 mg once weekly).